2020
DOI: 10.1155/2020/8780253
|View full text |Cite
|
Sign up to set email alerts
|

Baseline Levels of Serum Progesterone and the First Trimester Pregnancy Outcome in Women with Threatened Abortion: A Retrospective Cohort Study

Abstract: Objective. The relationship between serum progesterone and the first trimester pregnancy outcome of threatened abortion is still controversial. Therefore, we aimed to further study the association between these two parameters. Methods. The present study is an observational retrospective cohort study. A total of 726 participants who had threatened abortion from a hospital in Guangdong, China, were included in this study from 17th August 2011 to 30th October 2018. The exposure variable and the outcome variable w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
14
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 32 publications
0
14
0
1
Order By: Relevance
“…The combination of β-hCG and progesterone has been used to predict the prognosis of pregnancy outcomes in women who conceived naturally or via ART [ 12 , 18 ]. According to clinical experience, pregnant women undergo a large fluctuation in serum progesterone levels.…”
Section: Discussionmentioning
confidence: 99%
“…The combination of β-hCG and progesterone has been used to predict the prognosis of pregnancy outcomes in women who conceived naturally or via ART [ 12 , 18 ]. According to clinical experience, pregnant women undergo a large fluctuation in serum progesterone levels.…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that women with first‐trimester bleeding had an increased risk of pregnancy complications later 19 . Progesterone is commonly administered to pregnant women with threatened abortion or vaginal bleeding to prevent abortion 33,34 . In our study population, when asked the reason for progesterone used during pregnancy, the main answer was first‐trimester bleeding, followed by the low level of serum progesterone.…”
Section: Discussionmentioning
confidence: 93%
“…19 Progesterone is commonly administered to pregnant women with threatened abortion or vaginal bleeding to prevent abortion. 33,34 In our study population, when asked the reason for progesterone used during pregnancy, the main answer was first-trimester bleeding, followed by the low level of serum progesterone. Association analysis confirmed a statistically significant association between vaginal bleeding and maternal progesterone use.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the CI value of the TA group was decreased, and the ratio of the angle value lower than the upper limit of the normal reference value was higher than that of the NP group, indicating that the coagulation function is low, and there could be a problem of inadequate fibrin levels or function. Studies have shown a negative correlation between serum progesterone concentrations and early pregnancy outcomes, 19 and progesterone can promote thrombosis, 20 so that low progesterone concentrations may be the cause of reduced blood coagulation levels in TA patients. The CI value of the MA group was decreased, and the proportion of the MA value lower than the upper limit of the normal reference value was higher than that of the NP group, indicating that the patients may have low coagulation function due to low platelet count or function.…”
Section: Discussionmentioning
confidence: 99%